Determination of furan compounds in transformer oil by gas chromatography with new sorbents - A. A. Kartashova; V. F. Novikov (Известия высших учебных заведений: Проблемы энергетики)
Authors considered the question of selection of the optimal sorbent for gas chromatographic determination of impurity compounds in transformer oils. As promising sorbents are offered compositions with fixed liquid phase based on arilarsinovyh acids. They discussed the structure of the substituents on the aromatic ring of influence on selective properties. As the compound with an extreme selectivity offered para-methyl-fenilarsin acid.